Lactate minimum in a ramp protocol and its validity to estimate the maximal lactate steady state - Emerson Pardono; Bibiano Madrid; Daisy Fonseca Motta; Márcio Rabelo Mota; Carmen Silvia Grubert Campbell; Herbert Gustavo Simões (Universidade Federal de Santa Catarina, 2009)
The objectives of this study were to evaluate the validity of the lactate minimum (LM) using a ramp protocol for the determination of LM intensity (LMI), and to estimate the exercise intensity corresponding to maximal blood lactate steady state (MLSS). In addition, the possibility of determining aerobic and anaerobic fitness was investigated. Fourteen male cyclists of regional level performed one LM protocol on a cycle ergometer (Excalibur-Lode) consisting of an incremental test at an initial workload of 75 Watts, with increments of 1 Watt every 6 seconds. Hyperlactatemia was induced by a 30-second Wingate anaerobic test (WAT) (Monark-834E) at a workload corresponding to 8.57% of the volunteer's body weight. Peak power (11.5±2 Watts/kg), mean power output (9.8±1.7 Watts/kg), fatigue index (33.7±2.3%) and lactate 7 min after WAT (10.5±2.3 mmol/L) were determined. The incremental test identified LMI (207.8±17.7 Watts) and its respective blood lactate concentration (2.9±0.7 mmol/L), heart rate (153.6±10.6 bpm), and also maximal aerobic power (305.2±31.0 Watts). MLSS intensity was identified by 2 to 4 constant exercise tests (207.8±17.7 Watts), with no difference compared to LMI and good agreement between the two parameters. The LM test using a ramp protocol seems to be a valid method for the identification of LMI and estimation of MLSS intensity in regional cyclists. In addition, both anaerobic and aerobic fitness parameters were identified during a single session.